Integrable Anisotropic Evolution Equations on a Sphere - Meshkov, A.G.; Balakhnev, M.Ju. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
V.V. Sokolov’s modifying symmetry approach is applied to anisotropic evolution equations of the third order on the n-dimensional sphere. The main result is a complete classification of such equations. Auto-Backlund transformations are also found for all equations.